2021
DOI: 10.1186/s40635-021-00412-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of succinylated gelatin (4%) fluid on urinary acute kidney injury biomarkers in cardiac surgical patients

Abstract: Background Fluid resuscitation is frequently required for cardiac surgical patients admitted to the intensive care unit. The ideal fluid of choice in regard to efficacy and safety remains uncertain. Compared with crystalloid fluid, colloid fluid may result in less positive fluid balance. However, some synthetic colloids are associated with increased risk of acute kidney injury (AKI). This study compared the effects of succinylated gelatin (4%) (GEL) with compound sodium lactate (CSL) on urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…TGF is the mechanistic link between PT dysfunction, oliguria, and reduced GFR in AKI [22]. The early involvement of the PT dysfunction across a broad range of AKI is suggested by initial rises in urinary GGT, NGAL, and cystatin C. These urinary PT biomarkers and also urinary KIM-1 and mitochondrial DNA copy numbers [36, 40, 41] can be considered early markers to identify patients who are at most risk of developing subsequent rises in serum creatinine and can be used as an early AKI outcome in testing interventions in phase II trials [68] (Fig. 3).…”
Section: Summary and Clinical Implicationsmentioning
confidence: 99%
“…TGF is the mechanistic link between PT dysfunction, oliguria, and reduced GFR in AKI [22]. The early involvement of the PT dysfunction across a broad range of AKI is suggested by initial rises in urinary GGT, NGAL, and cystatin C. These urinary PT biomarkers and also urinary KIM-1 and mitochondrial DNA copy numbers [36, 40, 41] can be considered early markers to identify patients who are at most risk of developing subsequent rises in serum creatinine and can be used as an early AKI outcome in testing interventions in phase II trials [68] (Fig. 3).…”
Section: Summary and Clinical Implicationsmentioning
confidence: 99%
“…However, evidence regarding the bene ts and harms of succinyl gelatin remains limited. Smart L [21] found that uid resuscitation after heart surgery with succinyl gelatin (4%) was related to the increase of biomarker concentration of renal tubular injury and dysfunction compared with crystalloid uid. Katona [22] similarly reported a signi cant association between gelatin administration and an increased risk for early postoperative AKI in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, high-dose gelatin infusion may increase the fibrinogen level. 28 According to one study, colloid-induced hemodynamic changes during fluid resuscitation are only temporary but may induce acute kidney injury 29 and coagulation disorders. 28 The incidence of these AEs increases as the cumulative dose increases.…”
Section: Discussionmentioning
confidence: 99%